MARDANA– THE MASSAGE TECHNIQUE (International Journal of Ayurveda and Pharma Research, 2020)
Snehana is a substance that brings oiliness or unctuousness. It is mainly of two types based on Prayoga (Mode of Application), Abhyantara and Bahya Sneha. Mardana is one among the Bahya Sneha, where it is a therapeutic massage with pressure performed simultaneously on both sides of the patient’s body with strokes synchronized in the same direction. There is very little explanation about Mardana in Samhitas. It is exclusively explained by Acharya Tiruka in his work ‘Angamardana’ where he explains different types of Mardana like Shushkanga Mardana (dry massage), Ksheeranga Mardana (massage using milk), Tailanga Mardana (massage using oil), Svayamanga Mardana (self massage), Yamalanga Mardana (mutual massage ) and Samanyanga Mardana (common massage) consisting of 26 Hastas. Mardana provides relief from ailments and soothes the patient, both mentally and physically. Because of the lack of adequate review and analysis, this method of Bahya Sneha is losing its significance from practices and concept remains unexplored. The reason for not being practiced like other Snehana procedures are because of the less understanding of the concept of administration, scattered and minimal textual references. Aims and Objectives: This article is aimed to elaborate the concept of Mardana in health and disease. Materials and Methods: Data are collected from ancient texts and recent research articles, supported with discussion and presented. Result: The present article is an attempt to understand Mardana in detail in terms of textual references and bring down Mardana into mainstream of practice.